The interaction of entrepreneurial orientation on the business performance of Small and Medium Industries in Bali - Rihayana, I Gede; M Arsha, I Made Risma; Suardhika, I Nengah (Universitas Ciputra Surabaya, 2024)
This study tests the Resource-Based View (RBV) theory based on the interaction of entrepreneurial orientation, namely proactiveness, innovativeness, and risk-taking, on the business performance of Small and Medium Industries (SMIs) in Bali. The population of this study is SMIs in Bali with a sample of 55 randomly selected companies. Data collection was conducted through a survey using a questionnaire with a 5-point Likert scale to obtain respondents' perceptions. Data analysis used descriptive analysis and inferential analysis with SEM-PLS method. The results showed that the three dimensions of entrepreneurial orientation have a significant influence on business performance. A proactive attitude allows companies to respond quickly to market changes, innovation encourages the creation of new products and services, while risk-taking allows the exploration of new opportunities. This research supports the RBV theory which states that a firm's unique resources and capabilities can create competitive advantage and improve business performance in a sustainable manner. performance in a sustainable manner.